Dry-forest tree species with large seeds and low stem specific density show greater survival under drought. (26th January 2019) - Krishnan, Lalitha; Barua, Deepak; Sankaran, Mahesh
Abstract: Tree establishment in tropical dry forests is constrained by drought-related seedling mortality during early stages of recruitment. Predicted increases in the duration of growing-season droughts in the future pose a significant threat to these ecosystems that could significantly alter their vegetation structure and composition. Here, we examined drought tolerance in seedlings of seven common dry-forest tree species from the Indian subcontinent. We conducted a dry-down experiment on 3-wk-old seedlings, and asked whether the key plant functional traits, specific leaf area (SLA), leaf dry matter content (LDMC), seed size and stem specific density (SSD) were good predictors of seedling growth under well-watered conditions, and survival during drought. Seedlings displayed substantial drought tolerance with most seedlings surviving for more than 2 wk under protracted drought. Seed size in combination with SLA predicted seedling growth under well-watered conditions and seed size predicted survival under drought. In contrast to our expectations, seedlings with lower SSD survived for longer without water. Our results suggest that dry-forest species will be differentially affected by the predicted increases in the duration of growing-season droughts, and detrimental effects will be more severe for species with smaller seeds.